Industrial Instruments Model RD-B103 Solu Bridge (1965)
A Solu bridge determines the dissolved solids in water by measuring its conductivity. Though a manufacturer's name is not apparent, this unit was probably part of the Industrial Instruments product line; U.S. patent 2263932 was assigned to the company in 1941. In 1965, Beckman Instruments acquired Industrial Instruments, Inc. The Cedar Grove, New Jersey-based company manufactured solution conductivity analyzers and other industrial instruments. The photograph probably dates to the time of the acquisition.
Keywords: Scientific apparatus and instruments; Electronic circuits; Beckman Instruments, Inc.; Bridge circuits